Drivers to utilise evidence-based practice among nurses: A study in tertiary military hospital in Saudi Arabia - Zakaria, Zukarnain; Samivaloo, Christina Micheal; Ismail, Mohd Roslan; Arumugam, Vijayesvaran (Edelweiss Applied Science and Technology, 2024)
Nurses' knowledge, facilitators, and barriers related to Evidence-based Practice (EBP) are among the main issues that may determine the readiness of nurses to practice EBP it in their clinical settings. To identify factors that facilitated or hindered the adoption of EBP and to evaluate nurses' readiness to implement EBPs for evidence-based decision-making. The quantitative study involved 300 nurses currently working in the organization studied and used Rogers' diffusion of innovation theory to evaluate the factors that promote or hinder the implementation of EBP in their work settings. The data were gathered using a questionnaire and has been analyzed descriptively and inferentially, specifically using one-way ANOVA and regression analysis. Simple regression analysis showed a significant link between nurses' knowledge of EBP and facilitating factors on their readiness to implement EBP. Multiple regression confirmed that knowledge of EBP significantly influences nurses' readiness. While job positions had an insignificant impact, years of experience moderately influenced EBP readiness, and higher qualifications were positively correlated with readiness. The moderating effect of facilitating factors or barriers was not significant. The findings suggest that nurses' readiness to implement EBP is more influenced by their knowledge of EBP than by the barriers they face or the facilitating factors they receive. Nurses' knowledge towards EBP are crucial in determining their readiness to implement EBP in the healthcare settings. Hence, the healthcare organizations should emphasize improving their knowledge and ability to evaluate evidence by providing adequate education, training and support, develop protocols and guidelines and to fortify EBP readiness.